WITHHOLDING TAX ANALYSIS OF PERSONAL INCOME TAX FROM ONLINE GOLD TRADING - Wahyu Febri Lestari; Khojanah Hasan; Dwi Anggraini (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
As time progresses, people's interest in investing is increasing; therefore, many companies and institutions are opening investment services, ranging from low-risk to high-risk investments, one of which is Loco Gold London. Gold is one type of commodity that is most in demand for investment purposes; besides that, gold is also a financial or economic standard, a foreign exchange reserve, and the main means of payment in several countries. Gold investment is the most popular investment among investors because gold has low risk (the value of gold tends to rise every year) and high liquidity (Suharto, 2014). Online gold trading is carried out by personal traders (individual traders who use the services of domestic and foreign brokers). Technological advances and the increasing ease of access to information are currently greatly influencing the popularity of online trading. This is because brokers from various countries are emerging. It uses the latest technological facilities to make it easier for a trader to enter the market, analyze the market, and make decisions to take the right position.